Envirotyping helps in better understanding the root cause of success and limitations of rainfed production systems - Sawargaonkar, Gajanan L.; Davala, Moses Shyam; Rakesh, S.; Kamdi, Prasad J.; Khopade, Rohan Y.; Nune, Rajesh; Pasumarthi, Rajesh; Choudhari, Pushpajeet; Datta, Aviraj; Akuraju, Venkata Radha; Dixit, Sreenath; Singh, Ramesh; et al. (Frontiers in Environmental Science, 2024)
The current diagnostic agronomy study of the Bankura region of West Bengal, India, examined the variations in crop yields through a socio-ecological analysis of multiple production system components. Envirotyping for root cause analysis was employed to delve into the variables that affect the performance of rainfed production systems. Mother Earth, man, machine, management, and materials (5Ms concept) were the five indicators under which the variables were grouped. Findings demonstrated the fragility of the region’s soils due to its undulating terrain, unpredictable rainfall patterns, and frequent drought scenarios. The LULC’s NDVI showed that the agricultural area is about 60% and 43% of the total geographical area in the Hirbandh and Ranibandh blocks, respectively. Soils are acidic and diagnosed with deficiency of both macro and micronutrients (phosphorous, sulfur, and boron) having poor water holding capacity (35 to 55 mm for a 50 cm soil depth). The sand and soil organic carbon contents ranged between 43.04%–82.32% and 0.17%–1.01%, respectively with a low bacterial population. These factors are the root cause for low cropping intensity (106%) and low paddy productivity (3,021 kg/ha). Overall, the study contributes to designing and scaling-up of sustainable landscape management practices that could ensure higher cropping intensity and system productivity in similar agro-ecologies with limited evidence.